THE EMBODIMENT OF VOLUNTARY COMPLIANCE THROUGH UNDERSTANDING OF MSMEs TAX COMPLIANCE PERCEPTION - I Nyoman Darmayasa; Ni Wayan Desy Widhi Utami; I Nyoman Mandia (Universitas PGRI Madiun, 2021)
ABSTRACTThis research aims to understand micro, small and medium-sized enterprises' (MSMEs) perception of tax compliance as an embodiment of voluntary compliance. This study uses a qualitative interpretive method. The results show the fulfillment of MSMEs taxation is affected by the application of fines/sanctions, tax audits, tax knowledge, tax education, trust in tax authorities, a fair tax system, social norms, and ease of tax administration. These factors internalize into a value in the self of MSMEs, which is reflected through behavioral compliance. The shaping of positive tax perception is capital to realize tax awareness. The study results contribute to the realization of MSMEs compliance, both tax authorities and MSMEs.ABSTRAKPenelitian ini bertujuan untuk memahami persepsi wajib pajak usaha mikro kecil menengah (WP UMKM) tentang kepatuhan pajak sebagai bentuk perwujudan kepatuhan sukarela. Penelitian ini menggunakan metode interpretif kualitatif. Hasil penelitian menunjukkan bahwa pemenuhan kewajiban perpajakan WP UMKM dipengaruhi oleh penerapan denda/sanksi, pemeriksaan pajak, pengetahuan perpajakan, edukasi, kepercayaan terhadap otoritas pajak, sistem pajak yang adil, nilai sosial, dan kemudahan administrasi perpajakan. Faktor-faktor ini diinternalisasi menjadi sebuah nilai dalam diri WP UMKM yang kemudian tercermin melalui perilaku kepatuhannya. Pembentukan persepsi pajak yang positif merupakan modal untuk mewujudkan kesadaran pajak. Hasil penelitian berkontribusi terhadap perwujudan kepatuhan baik otoritas pajak maupun WP UMKM.